GIS-based multi-criteria decision analysis for parking site selection - Ozturk, Derya; Kilic-Gul, Fatmagul (ACADEMIC PUBLICATION COUNCIL, 2020)
Site selection is one of the strategic decisions in spatial planning and requires the consideration of many factors. Integration of Geographic Information Systems (GIS) and Multi-criteria Decision Analysis (MCDA) are useful for solving complex spatial decision problems such as site selection. In this study, integration of GIS and the Ordered Weighted Averaging (OWA) method, which is one of the most widely used MCDA methods in spatial decision problems, were used to analyze a parking site selection problem in Atakum (Samsun, Turkey). A GIS-OWA tool was developed in ArcGIS 9.2 via ArcObjects/Visual Basic for Applications (VBA), and a decision analysis for parking site selection was performed. Because the OWA method is based on parameters with mainly fuzzy quantifiers, by changing these parameters, a broad decision strategy set could be formed. Different scenarios provided a flexible approach for problem solution and the result obtained for delta=1 was compared with the present and planned parking sites. A comparison of the results showed that present and planned parking sites in the urban plan do not meet parking needs in Atakum (Samsun, Turkey).
Keywords: Geographic information system; GIS-OWA; multi-criteria decision analysis; ordered weighted averaging; parking site selection; LAND-USE CHANGES; MODEL; INFORMATION; SYSTEMS; RISK; CITY; Science & Technology - Other Topics